2010
DOI: 10.4161/bbug.1.2.11102
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered viral vectors for targeting and killing prostate cancer cells

Abstract: Enabling the transduction of therapeutic gene expression exclusively in diseased sites is the key to developing more effective treatments for advanced prostate cancer using viral-based therapy. While prostate cancers that express high levels of HER-2 are resistant to the killing effects of trastuzumab, they can be targeted for selective gene expression and destruction by lentiviruses with envelope proteins engineered to bind to this therapeutic antibody. More importantly, after intravenous injection, this tras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The second approach is based on a viral-based delivery system for biopharmaceuticals such as proteins, peptides, and non-coding small RNAs. Most viruses can be engineered to express anti-cancer protein-coding genes; indeed, many recombinant viruses infect specific target cells and express anti-cancer proteins [23,24,25]. Logistically, these viral delivery systems are easier to develop and use than other immunotherapy strategies such as whole tumor cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…The second approach is based on a viral-based delivery system for biopharmaceuticals such as proteins, peptides, and non-coding small RNAs. Most viruses can be engineered to express anti-cancer protein-coding genes; indeed, many recombinant viruses infect specific target cells and express anti-cancer proteins [23,24,25]. Logistically, these viral delivery systems are easier to develop and use than other immunotherapy strategies such as whole tumor cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Expressing high levels of HER-2, prostatic cancer cells, are resistant to monoclonal antibodies. They showed that the lentiviruses with envelope proteins destroyed the resistant prostate cancer cells by binding to the therapeutic antibody (17). In 2011, Balaggan and Ali used lentivirus in ocular diseases and transmitted the gene into retina cells (18).…”
Section: Discussionmentioning
confidence: 99%
“… Survivin 39 , 40 , 60 , 61 , 63 liver cancer, gastrointestinal cancer, gallbladder cancer, etc. HER-2 40 , 41 prostate cancer, breast cancer, pancreatic cancer, etc. uPAR 42 , 43 colorectal cancer, colon cancer, pancreatic cancer, breast cancer, etc.…”
Section: Main Textmentioning
confidence: 99%